PENDIDIKAN KARAKTER TERHADAP SISWA-SISWI SMK DI ERA LITERASI DIGITAL - Pratama, Widhy Andrian (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Community Service Activities (PKM), this is basically a form of initiative from the Lecturer of the Law Study Program, Syekh Yusuf Al-Makassari University, Gowa, in implementing the Tri Dharma of Higher Education, which is considered good and useful for character education for students of Syekh Yusuf Al-Makassari Gowa Pharmacy Vocational School. And this activity is carried out by presenting percentage material and direct interaction responding to students' responses. Community Service Activities (PKM), this was carried out on Thursday, July 25, 2024, at Syekh Yusuf Al-Makassari Gowa Pharmacy Vocational School. Which is located and located on Jl Andi tonro Permai, Tombolo, Somba Opu, Gowa Regency. So it can be concluded that Community Service Activities (PKM), this has been carried out up to providing knowledge in the form of presentations and also providing an understanding of digital literacy learning which is an effort to improve the learning process for students of Syekh Yusuf Al-Makassari Gowa Pharmacy Vocational School. This PKM activity ran orderly and smoothly. The students actively answered questions raised by the speakers and the school also felt helped by this PKM activity, because it could be an inspiration or input for educators in teaching in schools. And we also as the PKM implementation team hope that activities related to the utilization or use of digital technology for the learning process in schools can be held again